MAIZE YIELD CULTIVATED UNDER DIFFERENT ROW SPACING - Meira, Matheus José; Castilho Beruski, Gustavo; Tezzoto-Uliana, Jaqueline Visioni (REVISTA DE AGRICULTURA, 2022)
In corn crop, the correct determination of row spacing, and plant population can produce improvements in the yield. However, it is necessary to manipulate the spatial arrangements to aim for a better distribution of the plants, thus improving the use of cultivation resources. The work aimed to evaluate the corn yield under different row spacing. The experiment was carried out in the municipality of Angatuba, State of São Paulo, Brazil (23.4° S, 48.26° W and altitude of 535 meters). The sowing was done made on 16 December 2019. The hybrid P4285VYHR was sown, adopting a plant population of 65,000 plants ha-1. The treatments evaluated were: T1 - twin-row configuration, using the distance of 0.2 and 0.7 meters; T2 – row spacing of 0.6 meters; and T3 - 0.7-meter line spacing. The experimental design was blocks, arranged in bands, with five (5) repetitions. The variables evaluated were as follows: the average number of grains per ear (NGE); the mass of one hundred grains (MHG); and the final yield (PROD). The data was subjected to the variance analysis (ANOVA), and subsequently to the Tukey test. Analyzing the variable NGE, it was found that T1 presented a lower value compared to the other treatments, which presented values of 622.6 and 642.6 grains per ear, in treatments T2 and T3, respectively. Regarding the PROD variable, it was found that in T1, using the twin-row configuration, the result was 6586.0 kg ha-1, providing an increase of 12.15% and 19.16% compared to yield obtained in the T2 and T3, respectively. For the MHG, there was no statistically significant variation among the treatments used.